2018
DOI: 10.1152/ajpgi.00261.2017
|View full text |Cite
|
Sign up to set email alerts
|

Linaclotide improves gastrointestinal transit in cystic fibrosis mice by inhibiting sodium/hydrogen exchanger 3

Abstract: Gastrointestinal dysfunction in Cystic Fibrosis (CF) is a prominent source of pain among patients with CF. Linaclotide, a Guanylate Cyclase C (GCC) receptor agonist, is an FDA-approved drug prescribed for chronic constipation, but has not been widely utilized in CF, as the cystic fibrosis transmembrane conductance regulator (CFTR) is the main mechanism of action. However, anecdotal clinical evidence suggests that linaclotide may be effective for treating some gastrointestinal symptoms in CF. The goal of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 74 publications
2
27
0
Order By: Relevance
“…Linaclotide is a drug that has been approved by FDA to treat chronic idiopathic constipation. This study demonstrated that this drug elevates the amount of fluid in the intestinal lumen and improves intestinal transit, thus prompting the authors to recommend linaclotide as a therapeutic option to treat CF intestinal manifestations (Than et al, 2016; McHugh et al, 2018a).…”
Section: Murine Models In Cystic Fibrosis Researchmentioning
confidence: 92%
See 1 more Smart Citation
“…Linaclotide is a drug that has been approved by FDA to treat chronic idiopathic constipation. This study demonstrated that this drug elevates the amount of fluid in the intestinal lumen and improves intestinal transit, thus prompting the authors to recommend linaclotide as a therapeutic option to treat CF intestinal manifestations (Than et al, 2016; McHugh et al, 2018a).…”
Section: Murine Models In Cystic Fibrosis Researchmentioning
confidence: 92%
“…In a recent study, McHugh et al (2018a) generated a G542X CF mouse model with CRISPR/Cas9 gene editing method. 40.9% of founder mice expressed the G542X mutation and this new clone was generated in approximately 3 months, whereas traditional methods using embryonic stem cells, would necessitate 1–2 years to obtain the desired mouse colony.…”
Section: Murine Models In Cystic Fibrosis Researchmentioning
confidence: 99%
“…The CFTR corrector ivacaftor improves intestinal HCO 3 – secretion and nutrient absorption in individuals with CF [250] . The mode of action of the anti-constipation drug linaclotide (LINZESS®: a guanylate cyclase C receptor agonist) encompasses both paradigms by the cGMP-mediated reduction of NHE3 [251] and activation of CFTR activities [252] .…”
Section: Applications By Organ Systemmentioning
confidence: 99%
“…All three agents result in low systemic exposure and have been approved for the treatment of constipation‐prone irritable bowel (IBS‐C) syndrome. Despite an interest to apply these agents in the fight against CF‐associated intestinal disease (De Lisle, Mueller, & Roach, 2010; McHugh et al, 2018; O'Brien, Anderson, & Stowe, 2011), the efficacy of these agents to increase gut fluidity and alkalinity in vivo is currently unknown. Therefore, small and large intestinal fluid movements and bicarbonate output were assessed in cftr −/− , F508del mut/mut and WT mice in vivo .…”
Section: Introductionmentioning
confidence: 99%